2018
DOI: 10.3390/nu10030364
|View full text |Cite
|
Sign up to set email alerts
|

Association between Sarcopenia and Metabolic Syndrome in Middle-Aged and Older Non-Obese Adults: A Systematic Review and Meta-Analysis

Abstract: The associations between sarcopenia and metabolic syndrome (MetS) in non-obese middle-aged and older adults remain controversial. Thus, this meta-analysis aimed to evaluate the overall prevalence of MetS and the correlations between sarcopenia and MetS in middle-aged and older non-obese adults. We performed a systematic searched strategy using PUBMED, EMBASE and Web of Science databases for relevant observational studies investigating sarcopenia and MetS up to 11 May 2017. The polled prevalence of MetS and odd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
117
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(123 citation statements)
references
References 47 publications
6
117
0
Order By: Relevance
“…Then, we chose the newest meta‐analysis with the largest number of studies. Finally, 54 health‐related outcomes extracted from 30 meta‐analyses 10,22‐50 were reported in this umbrella review. These 54 outcomes were mainly about prognostic outcomes of tumor, postoperative outcomes, age‐related outcomes, metabolic outcomes, and other outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Then, we chose the newest meta‐analysis with the largest number of studies. Finally, 54 health‐related outcomes extracted from 30 meta‐analyses 10,22‐50 were reported in this umbrella review. These 54 outcomes were mainly about prognostic outcomes of tumor, postoperative outcomes, age‐related outcomes, metabolic outcomes, and other outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, they favoured the expression suitable to the assumed protective effect of FFM in health. Many studies used FFM% in large cohorts and also concluded that greater FFM was protective against insulin resistance (IR) and T2D, MetS, or cardiovascular disease risks . However, the use of FFM% per se is problematic because it inherently represents FM and FFM as well.…”
Section: ‘Unexpected’ Resultsmentioning
confidence: 99%
“…This article stems from contradictory published results in the literature concerning the beneficial role of greater fat‐free mass (FFM) on metabolic health . The widely accepted principle that greater FFM contributes to a better metabolic health overshadows available data supporting the opposite view.…”
mentioning
confidence: 99%
“…Age-related transient chronic inflammation imposes direct degenerative muscular effect [188] and indirectly causes oxidative stress, promoting the progression of sarcopenia. In addition, the relationship between MetS and sarcopenia has been established [189]. Obesity increases adipocytes followed by an elevation of adipokines, which causes muscle catabolic activity and increment of inflammatory cytokines [190,191].…”
Section: Effects Of Tocotrienol On Muscle Diseasesmentioning
confidence: 99%